1997
DOI: 10.1124/mol.52.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Structure/Activity Relationships in Lysophosphatidic Acid: The 2-Hydroxyl Moiety

Abstract: Although lipid phosphoric acid mediators such as lysophosphatidic acid (LPA) are now recognized widely as intercellular signaling molecules, the medicinal chemistry of these mediators is poorly developed. With the goal of achieving a better understanding of the structure activity relationships in LPA, we have synthesized and tested a series of LPA analogs that lack the 2-hydroxyl moiety. Our series consisted of compounds with 2, 3, or 4 carbon diol or amino alcohol backbones and oleoyl or palmitoleoyl acyl gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 34 publications
4
34
1
Order By: Relevance
“…Furthermore, FAPs lack the glycerol backbone; thus, the present findings provide compelling evidence that it is not required for ligand activity. These observations are in complete agreement with earlier structure-activity studies in which LPA receptors showed a high degree of tolerance to analogs with serine, tyrosine, or ethanolamine in place of the glycerol backbone (Sugiura et al, 1994;Jalink et al, 1995;Lynch et al, 1997;Hooks et al, 1998).…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, FAPs lack the glycerol backbone; thus, the present findings provide compelling evidence that it is not required for ligand activity. These observations are in complete agreement with earlier structure-activity studies in which LPA receptors showed a high degree of tolerance to analogs with serine, tyrosine, or ethanolamine in place of the glycerol backbone (Sugiura et al, 1994;Jalink et al, 1995;Lynch et al, 1997;Hooks et al, 1998).…”
Section: Discussionsupporting
confidence: 82%
“…1,2-Dioleoyl-sn-glycero-3-phosphoethanolamine (DOPE), 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC), 1,2-dioleoyl-sn-glycero-3-phosphate (monosodium salt; DOPA), 1,2-dioleoyl-sn-glycero-3-phosphoserine (sodium salt; DOPS), 1-oleoyl-sn-glycero-3-phosphate (sodium salt; LPA), and 1-oleoyl-sn-glycero-3-phosphocholine (LPC) were purchased from Avanti Polar Lipids (Birmingham, AL). 1-Oleoyl-3-(phosphoryl)propanediol (dehydroxy-LPA) was synthesized as reported previously (22). Lipid purity was checked by thin-layer chromatography and judged to be >99%.…”
Section: Methodsmentioning
confidence: 99%
“…Calcium and cAMP Assays-Calcium mobilization assays were performed as described previously by us (13). Briefly, intercellular calcium fluxes were measured on cell populations (2-4 ϫ 10 6 cells) that had been loaded with the calcium-sensitive fluorophore, INDO-1.…”
Section: Methodsmentioning
confidence: 99%
“…In a wide variety of tissue culture cells, LPA elicits Ca 2ϩ mobilization with an EC 50 of 0.2-10 nM (11,12), inhibition of cAMP accumulation with an EC 50 of 50 -100 nM (1,13,14), cell rounding (15), and other cytoskeletal rearrangements such as formation of stress fibers and focal adhesions (16), fibrinogen binding (17), and neurite retraction (18) also with nanomolar potency.…”
mentioning
confidence: 99%